Assessment of seasonal pattern of idiopathic sudden sensorineural hearing loss: a retrospective cross-sectional study. Issue 5 (20th May 2023) - Tal, O; Ibrahim, N; Ronen, O
Abstract: Background: A seasonal trend of patients with idiopathic sudden sensorineural hearing loss may direct research into possible aetiology. Methods: This study reviewed data from the medical records of patients who presented from 2004 to 2019 and who were diagnosed with new-onset idiopathic sudden sensorineural hearing loss. Seasonal pattern was assessed using chi-square and Rayleigh tests, and further confirmed by Monte Carlo simulation. Results: The study included 740 patients with a mean age of 48.3 years and a median age of 49 years. There was no statistical evidence for a difference in the distribution of sensorineural hearing loss cases for the four seasons of each year or with the cumulative data. New-onset idiopathic sudden sensorineural hearing loss cases averaged around 11 per month; there was no statistical evidence for a seasonal difference, as determined either by the Rayleigh test or with Monte Carlo simulation. Conclusion: There was no evidence to support the claim that idiopathic sudden sensorineural hearing loss incidence displays a seasonal pattern. More research is necessary to explore potential external factors such as climate or infection.